Glyceryl trinitrate in first-episode psychosis unmedicated with antipsychotics: A randomised controlled pilot study - Merritt, K; Catalan, A; Cowley, S; Demjaha, A; Taylor, M; McGuire, P; Cooper, R; Morrison, P (SAGE Publications, 2020)
Background: There is a pressing need for new classes of treatment for psychosis. A key therapeutic target for novel compounds is the NMDA receptor, which may be modulated by nitric oxide donors such as sodium nitroprusside (SNP). Recent studies of SNP in patients with psychosis have mixed results, and the drug has to be administered intravenously. Glyceryl trinitrate (GTN) is a well-established cardiovascular medicine that is also a nitric oxide donor, and can be given orally. Aims: We explored the safety and potential effects of GTN in unmedicated patients with a first episode of psychosis. Methods: This was a single-centre, randomised, double-blind, placebo-controlled trial from December 2016 to April 2019 (ClinicalTrials.gov identifier: NCT02906553). Patients received 3 × sprays of GTN or placebo for three consecutive days, and were re-assessed on Days 1, 2, 3 and 7. The primary outcome was cognition (Jumping to Conclusions task), secondary outcomes were symptoms (Positive and Negative Syndrome Scale (PANSS)), verbal memory (Hopkins Verbal Learning task), and mood (Bond–Lader Visual Analogue Scales). Results: Nineteen patients were randomised, and 13 participants were included in the analyses. Compared with placebo, GTN was well tolerated, but was not associated with significant effects on cognition, symptoms, or mood. Bayesian statistics indicate that our results were 2× more likely under the null hypothesis than the alternative hypothesis, providing anecdotal evidence that GTN does not improve psychotic symptoms. Conclusions: We found no indication of an effect of GTN on symptoms of psychosis or cognition.